Implications of virtual reality (VR) for school teachers and instructional designers: An empirical investigation - Ashraf Alam; Atasi Mohanty (Cogent Education, 2023)
AbstractThe present study involved an experimental inquiry wherein the researcher examined the possible impact of “textual cues” and “summarising scaffolding” on cognitive load, mental model, and learning performance. The study was conducted on a sample of 122 primary school pupils from Hyderabad, India. It commenced on 20 January 2021 and lasted till 28 October 2021. Using a randomization process, the participants were allocated to one of four experimental groups (D1, D2, D3, and D4). The results of the ANOVA analysis indicate that the utilisation of textual cues had a noteworthy and favourable effect on both the learning performance and the mental model. The implementation of summarising scaffolding yielded a remarkable enhancement in the mental model. The absence of significant “interaction effects” suggests that the implementation of immersive virtual reality, accompanied by textual cues or summarising scaffolding, can be advantageous for young learners. These discoveries hold particular significance for stakeholders involved in the field of education, particularly teachers and students, and possess noteworthy ramifications for the development of efficacious immersive learning environments.